(untitled) (Journal of Medical & Health Sciences Review, 2025)
Present experiment was performed to assess the toxicological impacts of pesticide dimethoate on haematological alterations in fish, Nile tilapia. Nile tilapia is a section feeder, omnivorous fish and mostly refined fish in South Asia. Fish were divided in three groups. One group was treated as control while second and third groups were exposed to 4 mg/L and 8 mg/L dimethoate respectively for 28 days. The most haematological change was severe microcytic hypochromic anemia. Results revealed that the value of HGB (control 5.53±0.40) (low 4.53±0.44) (high 3.10±0.51) (g/dl), RBC (control 2.47±0.35), (low 1.78±0.98), (high 1.44±1.4) (x106/ µL), HCT (control 17.6±1.30), (low 13.6±1.45), (high 10.0±0.90) (%), MCV (control 111±1.34) (low 129±2.98) (high 135±3.6) (FL), MCH (control 33.2±113) (low 40.4±1.56) (high 43.6±1.91) (pg), MCHC (control 28.4±1.13) (low 36.5±1.72) (high 41.0±2.26) (g/dl), RDW-SD (control 76.4±2.52) (low 70.6±1.91) (high 60.5±1.40) (%), PDW (control 11.1±1.1) (low 8.62±0.83) (high 4.63±0.69) (%) and PCT (control 0.650±0.07) (low 1.02±0.22) (high 1.58±1.02) (%) were significantly reduced. WBC (control 20.9±1.10) (low 24.9±1.80) (high 29.9±3.22) (x103/µL), RDW (control 16.5±0.78) (low 19.5±1.22) (high 22.3±1.47), PLT (control 207±2.00) (low 199±3.06) (high 168±1.23) (x103/µL), MPV (control 9.27±0.88) (low 11.4±1.1) (high 19.2±1.78) (fl), neutrophils (control 17.2±0.862) (low 19.7±1.04) (high 27.9±1.84) (%), lymphocytes (control 82.1±1.06) (low 92.3±1.12) (high 4110±2.08) (%), monocytes (control 2.24±0.07) (low 3.11±0.25) (high 5.04±1.12) (%) and eosinophils (control 1.18±1.60) (low 1.89±1.87) (high 3.33±2.33) (%) were increased respectively as compared to pesticide free group. After the obtained results, it indicates that dimethoate has caused widespread toxic effects on aquatic organisms specially fish.